I'm lost in the sea with the following example of decomposition without loss of dependencies...

Let be the dependencies F= {A → BC, C → AD} R is decomposed in R¹(A,B,C) & R²(A,D) I want to know if such a decomposition is without loss of dependencies and without loss of information.

I understand that it is without loss of information but why is it without loss of dependencies?

It is said so because

  • F¹={A → BC, C → A, C → B} because C → A and C → B since decomposition of A → BC. I don't understand why C → A and C → B
  • F²={A → D} but why? A → BC, C → AD therefore A → AD, no?

C → D shouldn't be lost but isn't in F¹ nor in F². Why is it important to say that?

C → A (from F¹) and A → D (from F²) therefore, C → D

The result which I don't understand at all is that it is without loss of dependencies...


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Browse other questions tagged or ask your own question.